Mother brain : how neuroscience is rewriting the story of parenthood - Conaboy, Chelsea (Henry Holt and Company, 2022)
"A groundbreaking exploration of the parental brain that untangles insidious myths from complicated realities, Mother Brain explodes the concept of "maternal instinct" and tells a new story about what it means to become a parent. Chelsea Conaboy delves into the neuroscience to reveal unexpected upsides, generations of scientific neglect, and a powerful new narrative of parenthood"--